2012
DOI: 10.1109/led.2012.2191759
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Silicon Bandgap Narrowing in Uniaxially Strained MOSFETs Subjected to Tensile and Compressive Stress

Abstract: Experimental evidence is presented for silicon bandgap narrowing in uniaxially strained MOSFETs subjected to both tensile and compressive stress. For both n-channel MOSFETs with n + polysilicon gate and p-channel MOSFETs with p + polysilicon gate, the strain-induced threshold voltage shift (ΔV th ) can be explicitly approximated from the changes in silicon bandgap (ΔE g ) and carrier mobility (Δμ). From the measurements of both ΔV th and Δμ associated with the strain ε, a simple ΔE g model at low strain ε is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The assumption that MC-POLY comprises grains with lower stress sensitivity is also in agreement with its low I ON stress sensitivity, which is also orientation-dependent. As the tensile mechanical stress also results in a Si bandgap decrease [19], its presence in the structures can be expected to degrade the I OFF . As the Si bandgap sensitivity to tensile stress is 1.6 times lower than to compressive stress [19], and given the I OFF dependence on the bandgap (Fig.…”
Section: B Impact Of Mechanical Stress On I Offmentioning
confidence: 99%
“…The assumption that MC-POLY comprises grains with lower stress sensitivity is also in agreement with its low I ON stress sensitivity, which is also orientation-dependent. As the tensile mechanical stress also results in a Si bandgap decrease [19], its presence in the structures can be expected to degrade the I OFF . As the Si bandgap sensitivity to tensile stress is 1.6 times lower than to compressive stress [19], and given the I OFF dependence on the bandgap (Fig.…”
Section: B Impact Of Mechanical Stress On I Offmentioning
confidence: 99%
“…Lu et al also reported a sharp point in the bandgap versus mechanical stress curve at zero strain according to their computer simulation [5]. Recently, Kang provided experimental evidence that there is indeed a sharp point in the bandgap versus mechanical strain curve at zero strain and the bandgap of silicon becomes smaller for both tensile strain and compressive strain [6]. However, as shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…The small shift of the graphs (Figure 4) between the flat and the bent states lies into the reproducibility of our measurement setup. The theoretical background for this findings lie into the fact that the photons in the visible spectrum of light possess much larger energies in comparison with the bandgap of silicon, which under mechanical stress is getting narrower [10,11]. Hence, the optical absorption takes place mostly through the help of phonons, which enable the indirect transitions from the valence to the conduction band.…”
Section: Experiments and Discussionmentioning
confidence: 97%